The development of a project-based multimedia and its effectiveness in improving students’ higher order thinking skills about chemistry bonding concept - Kholid, Idkhom; Harizon, Harizon; Hasibuan, Muhammad Haris Effendi (Jurnal Pendidikan Kimia, 2024)
This study aimed to develop a learning multimedia which is based on project-based learning (PjBL) and to investigate its effectiveness in improving students’ higher order thinking skills (HOTS) in the concept of chemistry bonding. This study used a research and development (R&D) design involving the method of Lee and Owen which consisted of five stages namely analysis, design, development, implementation, and evaluation (ADDIE) to develop the intended multimedia. The effect of the developed multimedia use on students’ HOTS was investigated using a one group pretest-posttest experimental design with a class of secondary high school students in Jambi city Indonesia. The research of analysis towards the development process showed that the project-based multimedia learning was successfully developed using the ADDIE method. This involved some validation results from some experts that include the chemistry expert and media learning expert who declared that it was valid and feasible to use. The results of experiments showed that the implemented multimedia was effective in increasing the participant students' HOTS after the learning process. The effectiveness was affirmed by the paired t-test (p-value = 0.000<0.05) indicating that there was a significant difference between the students’ HOTS pretest and posttest. This effectiveness was confirmed by the N-gain value of 0.58 which means that the students had experienced 58% HOTS improvement. This can thus be concluded that the developed project-based multimedia was valid and effective in improving students’ HOTS in the concept of chemistry bonding.